The storied life of A.J. Fikry : a novel - Zevin, Gabrielle (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2014)
When his most prized possession, a rare collection of Poe poems, is stolen, bookstore owner A. J. Fikry begins isolating himself from his friends, family and associates before receiving a mysterious package that compels him to remake his life.
Keywords: Booksellers and bookselling -- Fiction; Bookstores -- Fiction; Widowers -- Fiction; Abandoned children -- Fiction; Man-woman relationships -- Fiction; Psychological fiction